A limbic circuitry involved in emotional stress-induced grooming - Mu, Ming-Dao; Geng, Hong-Yan; Rong, Kang-Lin; Peng, Rong-Chao; Wang, Shu-Ting; Geng, Lin-Ting; Qian, Zhong-Ming; Yung, Wing-Ho; Ke, Ya (Nature communications, 2020)
Prolonged exposure to negative stressors could be harmful if a subject cannot respond appropriately. Strategies evolved to respond to stress, including repetitive displacement behaviours, are important in maintaining behavioural homoeostasis. In rodents, self-grooming is a frequently observed repetitive behaviour believed to contribute to post-stress de-arousal with adaptive value. Here we identified a rat limbic di-synaptic circuit that regulates stress-induced self-grooming with positive affective valence. This circuit links hippocampal ventral subiculum to ventral lateral septum (LSv) and then lateral hypothalamus tuberal nucleus. Optogenetic activation of this circuit triggers delayed but robust excessive grooming with patterns closely resembling those evoked by emotional stress. Consistently, the neural activity of LSv reaches a peak before emotional stress-induced grooming while inhibition of this circuit significantly suppresses grooming triggered by emotional stress. Our results uncover a previously unknown limbic circuitry involved in regulating stress-induced self-grooming and pinpoint a critical role of LSv in this ethologically important behaviour. Self-grooming is a frequently observed repetitive behaviour in rodents that is believed to contribute to post-stress de-arousal. The authors identified a previously unknown limbic circuit that includes the ventral lateral septum in rats and is involved in regulating stress-induced self-grooming.